Emotional intelligence in children with special educational needs - Sandu, Mihaela Luminita; Bîrzu, Maria Isabela (Technium Education and Humanities, 2023)
Despite the vigorous discourse surrounding education, current measures remain insufficient for effectuating substantive benefits for children. Guaranteeing the holistic development of children, particularly those with special educational needs, necessitates the provision of universally high-caliber educational experiences. It is critical to cultivate competencies for self-regulation and management of emotions from an early age, which is instrumental in fostering emotional stability and equipping children with the resilience to navigate life’s adversities. Individuals with disabilities encounter significant societal disadvantages, arising not only from their inherent circumstances but also from societal reactions and the manner in which they are treated within these social structures. Therefore, in this thesis I have chosen to address two of the most relevant and important issues, the development of emotional and social skills in pre-school children, aged 3-6/7 years, with special educational needs. If this skill is not developed, it can affect the balance of mental health, leading to anxiety, depression, low mood and other repercussions. The role of emotions in each individual’s life is as important as life itself. First of all, it should be noted that emotions manifest themselves constantly and differently. Different motives and contexts can provoke positive or negative emotions that cause changes in people’s behaviour, the effectiveness and direction of decision-making, the formation of relationships and other aspects of everyday life. Emotional intelligence is an important skill for all children, including those with special needs. They may face unique challenges in developing emotional intelligence, but with appropriate support and interventions, they can still make progress. Once a child develops this skill, it becomes easier for them to control their behaviour, which will lead to optimal social interactions. A child’s behaviour can be influenced by how they analyse the emotions conveyed by the people they interact with. So the child shapes and modifies behaviour based on what is shared with him/her through the emotions expressed by others.